PESAN MORAL DALAM FILM RAYA ANDTHELASTDRAGON: ANALISIS SEMIOTIKA CHARLES SANDERSPIERCE - Rehina Fulky Hadida; Siswanta Siswanta (Solidaritas, 2025)
This study aims to identify the moral messages contained in the film Raya and the Last Dragon. The research uses a qualitative descriptive approach. Data collection was conducted using the documentation method. The data analysis technique applied is based on Charles Sanders Peirce's semiotic theory, which includes representamen, object, and interpretant. The data analysis process involves interpreting symbols found in the film Raya and the Last Dragon, including data selection, data presentation, and analysis guided by Peirce’s semiotic framework. The results of the study show that four scenes illustrate moral messages such as loyalty and honesty, independence and perseverance, solidarity, and responsibility. The implication found in this study is that ignoring these moral messages may lead to conflict or division, as depicted in Raya and the Last Dragon.   Keywords: moral message, film, Charles Sanders Peirce’s semiotics.